Driving Performance Through Intellectual Capital: A Moderated-Mediation Examination of Leadership and Training Under Policy Turbulence - Nababan, Patrick Marcos Lech Walesa; Murwani, Danardana; Efrata, Tommy Christian (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In Indonesian government organizations, complex relationships exist between leadership, training, intellectual capital, performance, moderated by policy turbulence. This study investigates the complex relationships between leadership style, training and development, intellectual capital, and organizational performance in Indonesian government organizations, examining the moderating role of policy turbulence. Using a cross-sectional survey design, data were collected from 328 Indonesian government organizations through stratified random sampling across geographic regions, organizational sizes, and policy environments. The research employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test hypothesized relationships. Results reveal that intellectual capital serves as a critical mediating mechanism between organizational investments and performance outcomes. Training and development emerge as the strongest predictors of intellectual capital formation, while leadership style demonstrates a limited impact on intellectual capital development. Most significantly, policy turbulence positively moderates the intellectual capital-performance relationship, contradicting conventional wisdom about environmental uncertainty’s negative effects. The findings suggest that policy instability enhances rather than diminishes the strategic value of knowledge assets. Organizations with strong intellectual capital are better positioned to leverage uncertain policy environments for enhanced performance through improved adaptability and strategic flexibility.